Morphological responses and tolerance of a tree native to the Brazilian Cerrado Astronium fraxinifolium Schott to boron toxicity - Leite, Marilaine Cristina Marques [UNESP]; de Araujo, Maycon Anderson [UNESP]; da Silva de Paiva, Wesller [UNESP]; Camargos, Liliane Santos [UNESP]; Martins, Aline Redondo [UNESP] (Springer Nature, 2022)
The indiscriminate use of fertilizers and chemical pesticides can lead to boron contamination of the soil. Decontamination in general is expensive and results in other impacts. Phytoremediation is a sustainable alternative for soil restoration. Astronium fraxinifolium Schott (Anacardiaceae) is a tree species native to the Cerrado that is considered to be a pioneer species and a selective xerophyte, and it has been widely used in the reforestation and restoration of degraded areas. This study set out to characterize the physiology and anatomy of A. fraxinifolium under different boron concentrations and to assess the tolerance and phytoremediation potential of the species. An experiment with a completely randomized design was conducted in a greenhouse. The carbon allocation and chlorophyll content of leaves of A. fraxinifolium were determined. Boron concentration and the species’ tolerance index were calculated from root and shoot samples. Levels of amino acids, proteins, total carbohydrates, starch, phenolic compounds, and anatomical analysis were also measured. A. fraxinifolium showed tolerance to boron concentrations in the substrate and accumulated a greater amount of the element in the aerial part, showing its phytoextraction ability. No significant differences were found in the physiology of A. fraxinifolium; however, some anatomical changes were observed. In the leaves, there were changes in the thickness of the abaxial surface of the epidermis and palisade and spongy parenchyma, and total leaf thickness, and in the roots, there were changes in the thickness of the phloem, diameter of vessel elements, and number of vessel elements per square millimeter. However, boron did not interfere in the development and survival of A. fraxinifolium, which points to the possibility that the species has phytoremediation potential.
Keywords: Astronium fraxinifolium; Boron; Morphological adaptations; Phytoremediation; Soil pollution; Tolerance